Group Decision Support System (GDSS) Untuk Evaluasi Penawaran Pekerjaan Konstruksi Menggunakan Metode AHP dan Borda - Ogiana, Gede; Wirastuti, Ni Made Ary Esta Dewi; Ariastina, Wayan Gede (Jurnal Teknologi Elektro, 2017)
Evaluation of bids by WG ULP has an important role in the selection of providers of construction work to determine the potential winner. A group decision support system is a system that can help the Working Group ULP Bali provincial government in making decisions with the ability to analyze the construction work provider selection criteria with AHP and Borda method. With GDSS bid evaluation, all members of the Working Group can evaluate the ULP provider offering construction work optimally based on the criteria of administrative, technical prices so as to improve the quality of the repair process of group decision-making. Both methods are used because there are two stages in the decision-making that decision of individual and group decision. The test results show that the system can be applied GDSS as decision support systems in the bid evaluation provider of construction work and decided the company's most worthy to be a winner